The Use of Gadget-Based Internet to Improve Learning Independence, Motivation and Outcomes for Elementary School Students (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2021)
This study explained the increase in learning independence, learning motivation, and learning outcomes in science learning through gadget-based internet for fifth-grade students. The study was a classroom action research conducted at an elementary school. The number of participants was 25 students. Data collection was carried out using an observation sheet, test questions, questionnaires, and documentation. The results and data analysis indicated that the use of gadget-based internet could improve learning independence, motivation, and outcomes in science learning. The increase in student’s learning independence can be seen from the first cycle as much as 16%, second cycle 36%, and third-cycle students who have high learning independence again increased to 60%. The increase of student’s learning motivation can be seen from the first cycle as much as 36%, second cycle 48%, and third-cycle students who have high learning motivation again increased to 64%. The increase in student’s learning outcomes can be seen from the first cycle. It was obtained that 60% had reached learning standard, the second cycle 76% had reached learning standard, and the third cycle, 88%, reached learning standards.